ANALISIS STRATEGI PEMASARAN BIZNET DAN INDIHOME DI SALATIGA MENGGUNAKAN GAME THEORY - Rivo Masinambow; Adi Nugroho (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
This research analyzes the marketing strategies of Biznet and Indihome in Salatiga city using game theory. Primary and secondary data were collected through surveys and interviews with potential and existing customers, which were then analyzed using game theory to determine optimal strategies for Biznet and Indihome. The results reveal that Biznet excels in internet speed, while Indihome has a price advantage. The optimal strategy for Biznet is a slight price increase with maintained high speed, while Indihome should slightly reduce prices and offer decent speed packages. By following these strategies, both companies can achieve equal profits. Deviating from these strategies may result in lower profits for either Biznet or Indihome. This research provides valuable insights for optimal decision-making in Salatiga's highly competitive market.